Futsal Passing: Using El Rondo Exercise - Mutaqin, Ahmad Zaenal; Budiman, Indra Adi; Indrayogi, Indrayogi (Universitas Majalengka, 2024)
The motivation for this research is a lack of competency with basic passing techniques. This inquiry focuses on the El Rondo Exercise Against Passing. The approach used in this investigation was exploratory. The population of this study consisted of 15 students who participated in the futsal extracurricular program at MA Siti Khadijah Sindangwangi Majalengka. The sample size was determined using total sampling, which included all 15 participants. A passing skill test is the tool used to gather data. The paired sample test was then used to process and evaluate the data. Tcount = 13.484 > Ttable = 2.145 was the result of the data from the pretest and posttest. The significance shows that the sig (2-tailed) value is 0.000. H0 is true since the significance level is less than or equal to 0.05. H0 is rejected and approved because the significance value is less than (α = 0.05). It is clear from the data analysis results that the el rondo training approach significantly affects the outcomes of futsal passing. Also recommended by the researchers is the usage of the el rondo training method for futsal training.